2013
DOI: 10.5897/jma11.033
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial activity of crude extracts of Vernonia amygdalina on clinical isolates

Abstract: The antibacterial activities and preliminary phytochemical screening of ethanolic and aqeous extract of Vernonia amygdalina was performed against clinical isolates obtained from University of Ilorin Teaching Hospital (UITH) which included Escherichia coil, Staphylococcus aureus and Pseudomonas aeruginosa. Generally, the ethanol extracts showed more activities than aqueous extracts in both samples. The extracts exhibited antibacterial activity against the test organisms (0.5 to 15.50 mm). The phytochemical scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In addition, a family of naturally occurring substances called saponins complexes with cholesterol to create holes in bilayers of cell membranes. Consequently, these substances may be employed as agents that lower or inhibit cholesterol [31]. However, this study revealed that the saponins levels in the samples fell in the order; bitter leaf > pumpkin > spinach which showed no significant difference among the samples.…”
Section: Phytochemical Screeningmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, a family of naturally occurring substances called saponins complexes with cholesterol to create holes in bilayers of cell membranes. Consequently, these substances may be employed as agents that lower or inhibit cholesterol [31]. However, this study revealed that the saponins levels in the samples fell in the order; bitter leaf > pumpkin > spinach which showed no significant difference among the samples.…”
Section: Phytochemical Screeningmentioning
confidence: 65%
“…Because of their extreme toxicity and pronounced bitter taste, alkaloids are employed by plants as a defense mechanism against invertebrate pests, microbial diseases, and herbivores [24,27]. Furthermore, according to Adetunji et al [31], alkaloids possess antispasmodic, antibacterial, therapeutic, and antimalarial characteristics, making them the most effective phytochemical. Highest concentration of alkaloid was found in bitter leaf.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Chaya leaves extracted contains phytochemicals such as tannins. According to Adetunji, Olaniyi, and Ogunkunle, (2013); Noer, Pratiwi, and Gresinta, (2018), tannins are active compounds derived from plants that have bitter taste. Therefore, the administration of chaya leaves extract changed the taste of drinking water to become bitter as the level of administration increased.…”
Section: Water Intakementioning
confidence: 99%
“…Diameters of inhibition zones were measured by calculating the difference between cork borer (5 mm) and the diameters of the inhibition. Chloramphenicol and dimethyl sucohoxide were used positive control and negative control respectively (Adetunji et al, 2013).…”
Section: Antimicrobial Activitymentioning
confidence: 99%